2020
DOI: 10.1136/annrheumdis-2019-216588
|View full text |Cite
|
Sign up to set email alerts
|

Salivary gland epithelial cells from patients with Sjögren’s syndrome induce B-lymphocyte survival and activation

Abstract: ObjectivePrimary Sjögren's syndrome (pSS) is characterised by chronic hyperactivation of B lymphocytes. Salivary gland epithelial cells (SGECs) could play a role in promoting B-lymphocyte activation within the target tissue. We aimed to study the interactions between SGECs from patients with pSS or controls and B lymphocytes.MethodsPatients had pSS according to 2016 European League Against Rheumatism/American College of Rheumatology criteria. Gene expression analysis of SGECs and B lymphocytes from pSS and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(52 citation statements)
references
References 31 publications
3
45
0
Order By: Relevance
“…The upregulation of adhesion and chemokine molecules, along with metabolic stress induced apoptosis initiates the recruitment of innate immune cells and triggers an interferon-related inflammatory cascade ( 1 ). Type I interferon production by plasmacytoid dendritic cells induces infiltrating leukocytes and epithelial cells to secrete B-cell activating factor (BAFF), which promotes B-cell survival and not only contributes to B-cell hyperactivity, but also acts as a mediator between innate and adaptive immunity ( 2 , 3 ). Local accumulation and sustained survival of autoreactive B cells promote the development of ectopic germinal centers (GCs), which establish the perfect niche for autoantibody production or lymphomagenesis ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…The upregulation of adhesion and chemokine molecules, along with metabolic stress induced apoptosis initiates the recruitment of innate immune cells and triggers an interferon-related inflammatory cascade ( 1 ). Type I interferon production by plasmacytoid dendritic cells induces infiltrating leukocytes and epithelial cells to secrete B-cell activating factor (BAFF), which promotes B-cell survival and not only contributes to B-cell hyperactivity, but also acts as a mediator between innate and adaptive immunity ( 2 , 3 ). Local accumulation and sustained survival of autoreactive B cells promote the development of ectopic germinal centers (GCs), which establish the perfect niche for autoantibody production or lymphomagenesis ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…We previously showed that SGECs sorted from primary SS and control SGs expressed IL7 RNA and that this expression was higher in SGECs from patients with primary SS than from controls (25). Given this finding, we hypothesized that SGECs could be a source of IL‐7 in primary SS.…”
Section: Resultsmentioning
confidence: 99%
“…Transcriptomic analyses on pSS salivary glands have revealed upregulated ISG transcripts in whole salivary gland biopsies [ 47 , 48 , 49 , 50 ] and epithelium-enriched fractions [ 51 , 52 ]. Protein expression of type I [ 14 , 53 , 54 ], type II [ 55 , 56 ], and type III IFNs [ 57 , 58 ] has been observed in salivary glands.…”
Section: Type I Ifn Signaling In Primary Sjögren’s Syndromementioning
confidence: 99%
“…Transcriptomic analyses of pSS-derived salivary gland have repeatedly found upregulation of multiple ISGs involved in cytosolic RNA-sensing pathways or type I IFN signaling [ 47 , 48 , 49 , 50 , 114 , 115 , 116 ]. These findings were most pronounced in salivary glands with extensive mononuclear cell infiltrates [ 50 , 51 , 52 , 114 , 117 ]. Prominent staining of RIG-I and MDA5 has primarily been observed in infiltrating immune cells [ 64 ], which may be a reflection of localized IFN production.…”
Section: Cytosolic Ifn-inducing Rna-sensing Pathways In Primary Sjmentioning
confidence: 99%